Yield Performance of Sorghum Varieties Treated With Organic Fertilizer in Sumbawa Regency - Bajhir , Yusuf; Kadafi , Muamar; Purnamasari , Ayu; Khairi, Alfassabiq (BPFP Universitas Bengkulu, 2025)
Sorghum is an ancient grain that has good performance and adaptation in extreme condition. The crop is a stress-resilient crop with highly productive NADP-ME type C4 photosynthesis and highly efficient nitrogen and water utilization. Sorghum also requires relatively less water than other important cereals such as maize and wheat. Sorghum cultivation is very suitable to be carried out in Sumbawa Regency because it has the characteristic of low rainfall. The most common obstacle that occurs in sorghum cultivation is not being able to maximize plant genetics and existing nutrients, so that plant yields are low. One of them is by applying organic fertilizer. The interest in the use of organic fertilizers is increasing due to polluting effects of chemical fertilizers in the aerial and soil environment and gradual decline in the soil fertility. The aim of this study was to determine the yield of plants with different doses of organic fertilizers and sorghum varieties in Sumbawa Regency. This research used Split Plot Design consisting of two plots. The main plot three sorghum varieties were evaluated including V1 = Bioguma, V2 = GBE Methane, and V3 = Sweetbetty. The subplot is the application of solid organic fertilizer including T0 = control, T1 = 50 g plant-1, T2 = 100 g plant-1, and T3 = 200 g plant-1. This study had 3 replications and 36 experimental units. The results show that organic fertilizer application doses can cause significant differences in root weight, dry weight, fresh weight, grain weight/plant, weight 1000 grains, productivity, panicle length, and flowering age. Then, different types of sorghum also cause significant differences in grain weight per plant, weight of 1000 grains, and productivity. The best productivity is found at 200 g plant-1 of organic fertilizer. Optimal fertilizer application produces better grain.